Development of Structured Essay Diagnostic Test of Chemistry (SEDToC) as an Instrument for Assessment of Learning Outcomes and Identification of Misconceptions in Reaction Rate Materials - Oktayola Silfitri; Zonalia Fitriza (Edukimia, 2023)
The learning outcomes by learners are influenced by several factors, one of which is that learners have difficulty understanding the concepts because of misconceptions. The development of a structured essay diagnostic test of chemistry in reaction rate aims to identify misconceptions and learning barriers, assess learning outcomes that converge a good instrument criteria in terms of validity, reliability, difficulty index, and discrimination index. The research has three stages, namely determining the content, obtaining information about students' misconceptions, and developing diagnostic tests. The SEDToC instrument was validated by 5 validators. The results indicate that the SEDToC instrument is valid and reliable with an I-CVI value of 1 and Cronbach Alfa value of 0.84. In instrument difficulty index obtained 30% of questions with easy criteria, 60% medium and 10% difficult question. In addition, the discrimination index indicated that 10% of questions in the poor category, 20% sufficient, 40% good, and the rest were categorized as very good.